"Amplifying Black Italian voices": An interview with Leaticia Ouedraogo. Issue 5 (3rd September 2022) - Ouedraogo, Leaticia; Fabbri, Giulia; Romeo, Caterina
ABSTRACT: This interview with writer and activist Leaticia Ouedraogo was conducted via email during May and June 2022. Ouedraogo discusses what the concept of intersectionality means to her on a personal, political, and theoretical level, and how it is necessary to adopt an intersectional perspective, along with a decolonial practice, to fight sexism and racism. Starting from her short story "Nassan Tenga" (published in the anthology Future. Il domani narrato dalle voci di oggi [Future: Tomorrow Narrated by the Voices of Today]), the author also discusses the consequences of racism from a psychological and inter-generational perspective. The themes of structural racism, white privilege, decolonization, and intersectionality are articulated by Ouedraogo within the Italian postcolonial context, where they take on specific meanings in light of Italy's (often removed) colonial history.